Networked Learning and the SIfT Model - Whitehouse, C. M.; Durbin, C. S.; Shah, H. U. (Proceedings of the International Conference on Networked Learning, 2002)
The New Opportunities Fund ‘ICT for Teachers’ initiative, aimed to deliver professional development training for all ‘serving’ teachers in the UK . The scale of the task, suggested that an alternative delivery format to traditional face-to-face training should be trialled. SIfT, as an approved training provider to the Government scheme, has created a highly structured model for designing and delivering course materials to remote learners, via a Virtual Learning Environment. The poster session includes a demonstration of SIfT content and illustrates the SIfT model, consisting of the ‘12 Unit grid’, ‘Coursework framework’, ‘virtual tutor’ and ‘navigational features’, developed within the virtual space.